Growth optimization of white turmeric (Curcuma zedoaria) plantlets with growth regulators gibberellins - Murgayanti, Murgayanti; Nuroktavianti, Fenny Dewi; Nuraini, Anne (Universitas Padjadjaran, 2023)
The addition of cytokinin to the multiplication of white turmeric (Curcuma zedoaria) seedlings in vitro proved effective in shoot multiplication, but the addition of high cytokinin concentrations could cause stunted shoots and stunted growth. The addition of the hormone gibberellins (GA3) is often used in tissue culture for shoot elongation, so increasing the viability of plantlets. The experiment aims to determine the effect of GA3 and obtain the best concentrations of GA3 consisting of 0.50, 1, and 1.5 ppm GA3 on optimizing the growth of zedoary plantlets. The experimental parameters included the number of shoots, roots, leaves, plantlet height, and chlorophyll content observed at 6 WAP after subculturing. The results showed that giving 1 ppm GA3 had the best effect on optimizing plantlets' growth, namely the growth component of the number of shoots and plantlets' height.